Design of Diarylheptanoid Derivatives as Dual Inhibitors Against Class IIa Histone Deacetylase and β-amyloid Aggregation - Chen, Liang-Chieh; Tseng, Hui-Ju; Liu, Chang-Yi; Huang, Yun-Yi; Yen, Cheng-Chung; Weng, Jing-Ru; Lu, Yeh-Lin; Hou, Wen-Chi; Lin, Tony E.; Pan, I-Horng; Huang, Kuo-Kuei; Huang, Wei-Jan; et al. (Frontiers in Pharmacology, 2018)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder with multiple etiologies. Beta-amyloid (Aβ) self-aggregation and overexpression of class IIa histone deacetylases (HDACs) are strongly implicated with AD pathogenesis. In this study, a series of novel diarylheptanoid derivatives were designed, synthesized and evaluated for use as dual Aβ self-aggregation and class IIa HDAC inhibitors. Among these compounds, 4j, 5c and 5e displayed effective inhibitions for Aβ self-aggregation, HDAC5 activity and HDAC7 activity with IC50 values of < 10 µM. The compounds contain three common features: (1) a catechol or pyrogallol moiety, (2) a carbonyl linker and (3) an aromatic ring that can function as an HDAC cap and create hydrophobic interactions with Aβ1-42. Furthermore, compounds 4j, 5c and 5e showed no significant cytotoxicity to human neuroblastoma SH-SY5Y cells and also exhibited neuroprotective effect against H2O2-induced toxicity. Overall, these promising in vitro data highlighted compounds 4j, 5c and 5e as lead compounds that are worthy for further investigation.